Implementasi Modul Ajar Di Sekolah Sekolah Dasar Negeri 3 Palangka Raya - Amanda Serafy Lumanauw; Resna Winandar; Selfina; Matius Timan Herdi Ginting (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The implementation of the "Loving Others" lesson plan/teaching module went well and supported the achievement of the established learning objectives. Students demonstrated improvements in understanding the meaning of love, respecting differences, and maintaining harmony within the school environment. Their positive attitudes were evident through their active participation in discussions and the neat and creative creation of Kindness Action Cards. With the addition of supporting media and more effective time management, learning in subsequent meetings is expected to be more optimal and have a greater impact on students’ character development.